Three new species of the genus Otacilia Thorell (Araneae: Phrurolithidae) from China - Fu, Lina; Jin, Chi; Zhang, Feng (Zootaxa, 2014)
Three new species of the spider genus Otacilia are diagnosed, described and illustrated from China: Otacilia fujiana sp. nov. (male, female), O. pseudostella sp. nov. (male, female) and O. zhangi sp. nov. (male).